Effectiveness of physical therapy interventions for patients with degenerative thoracolumbar kyphosis and chronic low back pain - Tanno, Takaaki; Mochizuki, Eriko; Shida, Natsumi; Ataka, Hiromi; Nobe, Izumi (Journal of Spine Research, 2023)
Introduction: Age-related degenerative thoracolumbar kyphosis negatively affects health including chronic low back pain, physical mobility, and quality of life (QOL). Exercise interventions are potentially effective treatments for affected patients. The aims of the present study were to determine the effects of physical therapy interventions for 3 months on flexed posture, walking ability and health-related QOL in patients with degenerative thoracolumbar kyphosis and chronic low back pain.Methods: The subjects were 111 patients with degenerative thoracolumbar kyphosis and chronic low back pain. All patients received physical therapy that targeted spinal mobility and postural alignment provided by physiotherapists once per week for 3 months. The exercise program consisted of standardized posture training, individual muscle strengthening exercises, and stretch-altered flexibility according to the patient's physical ability. The patients were divided into two groups: patients with a flexible kyphosis [group F] (n = 72) and those with a rigid kyphosis [group R] (n = 39). Outcome measures included gait speed, patient-reported QOL scores (Japanese Orthopaedic Association Back Pain Evaluation Questionnaire [JOABPEQ]), back pain (visual analogue scale [VAS]), and spinal sagittal alignment (the flexicurve-measured kyphosis index or radiographic sagittal parameters). All measurements were evaluated before and 3 months after the intervention.Results: Gait speed showed significant increases (p<0.01) in both groups. Preoperative JOABPEQ category scores for low back pain were significantly lower in group R than in group F. However, both groups achieved good functional outcomes, with similar scores at 3- month follow-up in the category of low back pain. There were no significant differences between the groups in the therapeutic effectiveness for the four categories, with the exception of lumbar function. Forty percent of the patients in group F and 50% in group R showed an improvement of VAS greater than 20 mm. Spinal sagittal alignment showed no significant improvement after the intervention in both groups.Conclusion: Although the intervention did not improve clinical measures of kyphosis, gait speed was significantly improved in both groups, and back pain was reduced in 40-50% of the patients after 3-month exercise interventions. Thus, regardless of spinal mobility, a kyphosis-specific exercise program could have beneficial effects on physical function in patients with thoracolumbar kyphosis and chronic low back pain.